18F-FDG PET/CT in the diagnosis of infective endocarditis - Salminen, Linnea (My University, 2024)
Background: Increased uptake of 18F-fluorodeoxyglucose (FDG) by positron-emission tomography/computed tomography (PET/CT) is one of the diagnostic criteria for prosthetic valve endocarditis (PVE). However, there is limited data on the diagnostic value of FDG PET/CT in diagnosing native valve endocarditis (NVE) and semi-quantitative parameters of FDG uptake. Purpose: The objective of this retrospective study was to evaluate the accuracy of FDG PET/CT and additional value of semi-quantitative measures of FDG uptake in the detection of NVE and PVE. Methods: All patients who had undergone FDG PET/CT due to suspected infective endocarditis (IE) at a single tertiary referral center between 2010 and 2020 were identified. Additional patients who underwent FDG PET/CT for detecting an infection focus were included as controls. Clinical reports were evaluated and images were analyzed for maximal standardized uptake value (SUVmax) and target to background ratio (TBR = SUVmax normalized to mean blood pool SUV) around valves. The scan was defined positive based on either clinical reading or previously proposed cut-off values for SUVmax and TBR (>4.2 and >2.1, respectively). The final diagnosis of IE was defined based on all available information in electronic medical records. Results: The study cohort included 16 patients with suspected NVE (median age 58 years, 88% male), 24 patients with suspected PVE (median age 72 years, 92% male) and 37 patients who underwent FDG PET/CT for detecting an infectious focus (8 with a prosthetic valve). The final diagnosis was definite IE in 25 (14 PVE), possible IE in 7 (6 PVE), and no IE in 45 (12 with a prosthetic valve). Overall, clinical reading of FDG PET/CT identified 17 (sensitivity 68%) of definite IE with a specificity of 91% and accuracy of 83%. Compared with NVE, the sensitivity of FDG PET/CT was higher in the detection of PVE (46% vs. 86%) whereas specificity was lower (97% vs. 75%) resulting in small difference in accuracy (84% vs. 81%). In PVE, SUVmax had higher sensitivity (93%) than clinical reading, resulting in the same accuracy (81%) despite lower specificity (67%). A combination of either positive clinical reading or positive SUVmax identified all patients with PVE (sensitivity 100%). In NVE, TBR had higher sensitivity (64%) than clinical reading, but accuracy (66%) and specificity (67%) were significantly lower. Conclusions: FDG PET/CT shows high sensitivity in the detection of PVE and high specificity in the detection of NVE in a real-world clinical cohort. Semi-quantitative parameters of FDG uptake can improve sensitivity of detecting PVE maintaining diagnostic accuracy. However, in NVE semi-quantitative parameters were associated with a prominent reduction in specificity.
Keywords: Infective endocarditis, PET, infection, inflammation